Perspectives on choral singing: Lembaga Hasil Dalam Negeri Malaysia (LHDNM) and Institut Tadbiran Awam Negara (Intan) / Nurul Nadiah Awang - Awang, Nurul Nadiah (Faculty of Music, 2016)
This study was involves investigation of two choral groups established by Lembaga Hasil Dalam Negeri Malaysia (LHDNM) and Institut Tadbiran Awam Negara (INTAN). The purpose of this mixed method research study is to gain insight into choir members' motivation for joining and continuing to participate in choirs. The researcher used a specially-developed questionnaire to survey the population of the community choir, and performed case studies of two selected choir members using semi-structured interviews. The questionnaire included three sections: a demographic profile of the choir singers; musical background and experience; self-evaluation results using Choral Music Participation Inventory (CMPI). Frequency tables were developed and cross-tabular analysis was performed to further understand the demographic composition of the choirs. The two semi-structured interviews revolved a research questions: "How do the LHDNM and INTAN set up their choirs?" with intention to seek detailed information of their preparation to make a set-up of choir in both government sectors LHDNM and INTAN and what motivates their participation in choral singing. Suggestions for future research are provided based on the key findings of this study.